Renovação Carismática Católica: a cura milagrosa como um espaço convergente entre religião e medicina - Silva, Sélcio de Souza (2011)
Our purpose of study and corpus research is the Catholic Charismatic Renewal, a Pentecostal hustle, introduced in the Roman Catholic Christian religious institution. The objective in this work is to understand the action of the sacred in any miracle purpose, our goal is to analyze the concepts of miracle cure in the Catholic Charismatic Renewal presented by the faithful, from their narratives about how they its impacts on personal and social life of those who took part in the experience of the miraculous phenomena, that is, cancer cure. Charismatic Renewal, thus enabling an environment conducive to the pursuit of religious offering (occurrence of miracles) to the sacred, from feelings as belief and supernatural faith, but without leaving the conventional treatment. Reestablishing them physical, psychic and emotionally, giving them a purpose (nomia) to their existence. It will be developed through a field research, supported in the sociological discussion of religion that will enable us to identify each Catholic Charismatic Renewal, beyond the therapeutic function, element as convener (because of its paradoxical character), between Religion and Medicine, faith and science. In particular, it will be focused through this labor, to analyze and present the experience of the miracle with a group of 7 (seven) women Brazil. For this current analysis, it will be used, in our fieldwork, two investigative methods: participant observation and implementation of two research questionnaires (self-applicable). Therefore we realize that religion, mainly the Catholic Charismatic Renewal is a way to provide its followers to try religion or it may lead to the meeting cancer. In Catholic Charismatic Renewal, the miracle cure comes as a converging space between Religion and Medicine because these two realities in modern ages are prone to reconnect towards the solution of modern problems. This encounter provides changes in the psychological and social behavior, because they correspond, respectively, a change in the order of the conscious and unconscious and, hence a behavioral intrapersonal and interpersonal change.